Besshumnye lidery . Besshumnye lidery . Silent Leaders . Бесшумные лидеры - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with Valery Ryzhik, a teacher of mathematics in the physics-technological school under Russian Academy of Sciences; segment of the new method of water purification. Интервью с Валерием Рыжиком, учителем математики физико-технической школы при Российской Академии Наук; сюжет о новом методе очистки воды.